Contribution of geographic information system to improve the insurance management of natural disasters in Algeria case study: the City of Batna - Ramoul, Sihem; Cemali, Nedjoua; A Chiha.A, Allouch (Italian journal of engineering geology and environment, 2022)
In recent years, the frequency of natural disasters has increased all over the world, including in Algeria. In the last decades Algeria has been marked by very largescale natural disasters: floods, landslides and earthquakes, which have caused considerable material damage and loss of life in view of the extent of the damage caused by natural disasters, the public authorities have decided to set up a special insurance system (CatNat ) based on the obligation to insure against the effects of natural disasters, in order to lighten the burden on the State in terms of reparations. This insurance was created in 2004 following damage caused by the floods in Bab El Oued and the earthquake in Boumerdes in 2001 and 2003 respectively. The increase in natural disasters and thus in the cost of claiming compensation encourages insurers to participate in the recovery and reduction of natural risks by improving their insurance management. The applications of Geographic Information Systems (GIS) to insurance management are numerous; and they allow, among other things, insurers to segment their pricing and to specialise the vulnerability of their insurance portfolios. Insurers support their management on natural risk, exposure and liability cards. Geographic information becomes crucial for insurers. This paper talks about clarified the role of insurers in the management of natural risks and how to promote better insurance management through the integration of geographic information system in the city Batna.